Performance Evaluation of Cryogenic Treated HSS Drill (Global Journals of Research in Engineering, 2013)
Tool wear is a worn portion over the flank and face of the tool. Tool wear is significant for determining tool life and hence it influences the machining economics. The wear measurements are carried by using a tool makers#x2019; microscope in the present investigations. All the investigations are carried in dry machining. Life enhancement by using cryogenic treatment on HSS drill (T1-type) is the objective of study. Investigations are carried on different work materials such as AA6041, AISI 1040 and EN36. Improvement in tool life up to 140% for AA6041, 90% for AISI 1040, 38% for EN36 is observed. These investigations are aimed at benefiting small industries that use aforementioned tool work combinations. Regressions models are constructed for wear for both untreated machining and cryogenic treated machining.
Keywords: drilling; cryogenic treatment; regression analysis; tool wear